Aplikasi Berbagai Konsentrasi Pupuk Plant Catalyst 2006 dan Gibberellin pada Tanaman Tomat (Lycopersicum esculentum Mill.) - Armaini '; Elza Zuhry; Gading Sahyoga (Jurnal Sagu, 2007)
The objective of this research was to observe the effect of interaction between plant catalyst 2006 fertilizer and gibberellins on the growth and yield of tomato. This research used Completely Randomized Design (CRD) which was arranged in factorial with two factors and three replications. The first factor was concentration of plant catalyst 2006 fertilizer (P) which consisted of P0 (0 g/l), P1 (1,0 g/l), P2 (I,5 g/l), P3 (2,0 g/l), and P4 (2,5 g/l). The second factor was Gibberellin (G) which consisted of G0 (0 ppm), G1 (50 ppm), G2 (75 ppm), G3 (100 ppm), and G4 (125 ppm). Parameters observed were plant height, total flower, harvesting time and fruit weight. The result of this research shows that interaction between plant catalyst 2006 fertilizer (2,0 g/l) and gibberellins (50 ppm) exhibited the best effect on harvesting-time of tomato production.